2020
DOI: 10.1093/cz/zoaa042
|View full text |Cite
|
Sign up to set email alerts
|

Polyphony of domestic dog whines and vocal cues to body size

Abstract: In domestic dogs Canis familiaris, vocal traits have been investigated for barks and growls, and the relationship between individual body size and vocal traits investigated for growls, with less corresponding information for whines. In this study, we examined frequency and temporal traits of whines of 20 adult companion dogs (9 males, 11 females), ranging in body weight from 3.5 to 70.0 kg and belonging to 16 breeds. Dog whines (26–71 per individual, 824 in total) were recorded in conditioned begging contexts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 90 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…pigs [28]), pitch itself (F0) is also an informative cue, especially in the widely varying morphology of dogs ( [22]; see Introduction). Indeed, since formant dispersion and F0 both vary in small to large dogs' vocalizations ( [21,29], Farago and colleagues have suggested that both could act as a cue to size in dogs ( [21]; see also [11] for other mammals). We must also consider the relevant ecological fact that dogs are perhaps the closest non-human domestic companion to humans themselves.…”
Section: Discussionmentioning
confidence: 99%
“…pigs [28]), pitch itself (F0) is also an informative cue, especially in the widely varying morphology of dogs ( [22]; see Introduction). Indeed, since formant dispersion and F0 both vary in small to large dogs' vocalizations ( [21,29], Farago and colleagues have suggested that both could act as a cue to size in dogs ( [21]; see also [11] for other mammals). We must also consider the relevant ecological fact that dogs are perhaps the closest non-human domestic companion to humans themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, experienced caregivers remained sensitive to whine f o when assessing distress, size and dominance. This suggests that f o may function as a reliable index of these traits in puppy vocalizations (as identified for distress and size in adult dog whines [55,56] and in the calls of other mammals [1,2]), a hypothesis that we are currently investigating.…”
Section: Discussionmentioning
confidence: 99%
“…However, in mammals, additionally to calls produced with phonation mechanism based on air flow‐induced vibrations of the vocal folds (Berke & Long, 2010; Herbst, 2014; Herbst et al, 2012) there are calls produced with another mechanism, the aerodynamic whistle, based on airflow vorticities in the vocal tract (Håkansson et al, 2022; Mahrt et al, 2016; Riede et al, 2017, 2022). Calls of the same individual animal produced with phonation mechanism have a substantially lower fundamental frequency than those produced with whistle mechanism (carnivores: Frey et al, 2016; Sibiryakova et al, 2021, artiodactyls: Reby et al, 2016; Volodin, Volodina, & Frey, 2017, rodents: Dymskaya et al, 2022; Fernández‐Vargas et al, 2022). In addition to cubs of cheetahs, cubs of other felids, as lynxes and pumas are capable of producing very high‐frequency calls, up to 5 kHz (Allen et al, 2016; Peters, 1987, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Calls of the same individual animal produced with phonation mechanism have a substantially lower fundamental frequency than those produced with whistle mechanism (carnivores: Frey et al, 2016;Sibiryakova et al, 2021, artiodactyls: Reby et al, 2016, rodents: Dymskaya et al, 2022Fernández-Vargas et al, 2022). In addition to cubs of cheetahs, cubs of other felids, as lynxes and pumas are capable of producing very high-frequency calls, up to 5 kHz (Allen et al, 2016;Peters, 1987Peters, , 2011.…”
Section: Comparison With Vocal Ontogeny Of Other Felidsmentioning
confidence: 99%